Water distribution systems handbook (McGraw-Hill, 1999)
Civil engineers and anyone else involved in any way with the design, analysis, operation, maintenance or rehabilitation of water distribution systems will find practical guidance in Water Distribution Systems Handbook. Experts selected by Handbook editor Larry W. Mays provide historical, present day, and future perspectives, as well as state-of-the-art details previously available only in specialized journals. You get a comprehensively detailed exploration of every facet of the hydraulics of pressurized flow; piping design and pipeline systems; storage issues; reliability analysis and distribution, and more. Detailed information on the latest technology contributions and on enhancements to the EPANET model are included. You'll also find case studies that range from the small municipal systems found in every U.S. town, to large systems common to great urban centers like New York, London and Paris.